Analisis Media Pembelajaran Daring Terhadap Penjaminan Mutu Pendidikan di Masa Pandemi Covid-19 - Mutmainah, Putri; Darmiyanti, Astuti (At- Ta'lim : Jurnal Pendidikan, 2022)
The use of online learning media during the covid-19 pandemic can be an alternative option to provide a sense of security in teaching and learning activities. This research aims to analyze the use of online learning media in the learning process in the pandemic against the quality assurance of education. Where in this paper, the author discusses about the media used in teaching and learning activities, about the effectiveness of the use of learning media, and finally about the obstacles or obstacles experienced by both students and teachers in the use of learning media in teaching and learning activities. This research was conducted in the neighborhood. The method used in this study is descriptive qualitative research methods, where in collecting information the author disseminates google form questionnaires to learners in the surrounding environment at every level, such as elementary, junior high, high school, and university. The result of this study is to get the information that will be needed for this writing. Among the results obtained from this study are knowing about the effectiveness and constraints of online media, applications used for the learning process, and efforts in ensuring the quality of education, as well as motivation and expectations for others and others